(-53).21 = (-53).(20 + 1) = (-53).20 + (-53).1 = -1060 + (-53) = -1113
Đúng 0
Bình luận (0)
(-53).21 = (-53).(20 + 1) = (-53).20 + (-53).1 = -1060 + (-53) = -1113
Thay một thừa số bằng tổng để tính: 75.(-21)
Thay một thừa số bằng tổng để tính
340.(-21)
(-13). 101
Thay một thừa số bằng tổng để tính:
a)-57.11
b)75.(-21)
Thay một thừa số bằng tổng để tính :
a)-57.11
b)75.(-21)
Thay một thừa số bằng tổng để tính nhanh:
a) (-34).11 b) 250. (-21)
c) (- 23).101 d) 31. ( -99)
Thay một thừa số bằng tổng để tính nhanh:
a) (-34).11 b) 250. (-21)
c) (- 23).101 d) 31. ( -99)
Thay một thừa số bằng tổng để tính
a) -57 . 11
b) 75 . (-21)
Thay một thừa số bằng tổng để tính :
a ) -57 . 11
b) 75 . ( -21 )